2011
DOI: 10.1111/j.1473-2165.2011.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermal penetration of creatine from a face-care formulation containing creatine, guarana and glycerol is linked to effective antiwrinkle and antisagging efficacy in male subjects

Abstract: In summary, creatine represents a beneficial active ingredient for topical use in the prevention and treatment of human skin aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Recent findings indicate that urea is a highly active substance with specific gene‐regulating activities which affect mRNA expression of certain genes involved in keratinocyte differentiation. Creatine helps to supply energy to cells increasing the formation of adenosine triphosphate (ATP) improving mitochondrial functions. Palmitoyl tripeptide‐38 is an amino acid chain which has demonstrated the capacity to increase the production of dermal and epidermal components such as collagen, fibronectin, and hyaluronic acid .…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings indicate that urea is a highly active substance with specific gene‐regulating activities which affect mRNA expression of certain genes involved in keratinocyte differentiation. Creatine helps to supply energy to cells increasing the formation of adenosine triphosphate (ATP) improving mitochondrial functions. Palmitoyl tripeptide‐38 is an amino acid chain which has demonstrated the capacity to increase the production of dermal and epidermal components such as collagen, fibronectin, and hyaluronic acid .…”
Section: Introductionmentioning
confidence: 99%
“…10 Other small molecules produced by LB244R® that may affect aging include taurine and creatine, both of which can alleviate aging. 21 The microbiome plays a role in aging as well. 3 Centenarians have higher levels of Lactobacillus and additionally, Lactobacillus present on skin reduces with age.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Peirano et al ( 2011) [51] demonstrated that guarana presented 23% higher cellular esterase activity than formulations without guarana, exerting a vitalizing effect on skin fibroblasts.…”
Section: Cytotoxicity Studiesmentioning
confidence: 95%
“…It is present in several cosmetic products, due to its antimicrobial [39][40] and antioxidant activity [34-36, 39, 41-50]. Due to the high content of alkaloids in guarana, extracts are added to products for the treatment of gynoid lipodystrophy and to anti-aging creams [51][52]. Given the importance of guarana and the increasing use of its seeds, there has been increased interest in the quality of the products containing this compound because its chemical structure is predominantly unsaturated and susceptible to oxidation [53].…”
Section: Introductionmentioning
confidence: 99%